Estudio ultraestructural de la epidermis foliar de Phaseolus vulgaris L - Flores, E.M.; Espinoza, A.M.; Kozuka, Y. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The epidermal cells of Phaseolus vulgaris L. were studied by means of a Scanning Election Microscope and the following results were obtained. The abaxial (lower) leaf epidermis showed greater variety of trichomes than the adaxial (upper) surface. The leaf is amphistomatic and has abundant stomata. The ostioles are small and become vendace toucids the stomatic chamber. Stomata are of the paralytic type. Small round structure showing a pour diet found in the scholar epidermis; a possible glandules function could be associated whit them. The venation is semicraspedodromons. Veins are pubescent abaxially and the areoles of irregular, sometimes polygonal shape.